Ecological effects of the European barbel Barbus barbus (L., 1758) (Cyprinidae) invasion on native barbel populations in the Tiber River basin (Italy) - A. Carosi; L. Ghetti; G. La Porta; M. Lorenzoni (The European Zoological Journal, 2017)
The purpose of this study was to investigate the effects of the European barbel Barbus barbus (L., 1758) invasion in the Tiber River basin (Italy) on the native Tiber barbel Barbus tyberinus Bonaparte, 1839, verifying whether the co-occurrence played a negative impact on growth rate and relative weight. Fish census data were collected during three periods (2000–2005, 2006–2010, 2011–2015) at 158 sampling sites. Since its first record in 1998, European barbel rapidly spread in the study area: it was present in more than 20% of the monitoring sites, where it is leading to the gradual replacement of Tiber barbel by widening its distribution in the Tiber River and in the downstream reaches of the main tributaries. By contrast, Tiber barbel has suffered from this competition, as demonstrated by the fact that the mean value of the relative weight was significantly higher where European barbel was absent. The results obtained suggested that this non-native species could be a serious threat to the conservation status of endemic Tiber barbel, and constitute the premise to underpin conservation strategies aiming to preserve native freshwater biodiversity.